Computerization of banking operation in Bangladesh - Raihan Kibria; Shafkat Reza Chowdhury; Saad Hasan; Mohammad Rashedul Hoque (International Journal of Technology for Business (IJTB), 2020)
This paper is about the computerization of the banking operation of two of the largest banks in Bangladesh. The discussion deals with the issues faced in rolling out Core Banking System (CBS) in Sonali Bank and Rupali Bank. The system we studied focuses on centralizing computing operations by consolidating IT infrastructure; this system is meant to replace the existing distributed computing components. In this paper, we will highlight both the technical and human issues we have faced. The paper highlights the context of the work, the scale of the problem, issues and challenges faced during the roll-out. The intricacies of implementing a large-scale system such as CBS are educational, but nevertheless daunting. The findings of the paper articulated that obstacles could be overcome through human ingenuity and discipline. The paper stresses that structural approach of software development is necessary for long-term success of a project and properly trained software professionals is integral to the development of a complex software project.
Keywords: 650; Bangladesh; Core Banking System; Banks; Software; Information Technology Infrastructure